RNA Regulatory Networks as a Control of Stochasticity in Biological Systems - Vandevenne, Marylène; Delmarcelle, Michael; Galleni, Moreno (Frontiers in Genetics, 2019)
The discovery that the non-protein coding part of human genome, dismissed as “junk DNA”, is actively transcripted and carries out crucial functions is probably one of the most important discoveries of the past decades. These transcripts are becoming the rising stars of modern biology. In this review, we have casted a new light on RNAs. We have placed these molecules in the context of life origins, evolution with a big emphasize on the “RNA networks” concept. We discuss how this view can help us to understand the global role of RNA networks in modern cells, and can change our perception of the cell biology and therapy. Finally, although high-throughput methods as well as traditional case-to-case studies have laid the groundwork for our current knowledge of transcriptomes, we would like to discuss new strategies that are better suited to uncover and tackle these integrated and complex RNA networks.